2018
DOI: 10.4103/ijp.ijp_239_18
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of pharmacology education in India: Past and future

Abstract: Pharmacology education has passed through various stages in the evolution sequence due to ever-changing type and repository of drugs as well as technological advancements in the educational processes. This article reviews the journey of evolution of pharmacology education. Pharmacology is relevant component of various curricula in medical, dental, and paramedical courses. A huge number of students learn pharmacology as a subject. Important milestones in evolutionary sequence included revisions and updates in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Revisions and updates to learning objectives, teaching-learning materials and techniques, and evaluation at the Undergraduate (UG) and Postgraduate (PG) levels were significant turning points in the evolutionary sequence. Teaching and evaluation methodologies used for pharmacology are undergoing several improvements [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Revisions and updates to learning objectives, teaching-learning materials and techniques, and evaluation at the Undergraduate (UG) and Postgraduate (PG) levels were significant turning points in the evolutionary sequence. Teaching and evaluation methodologies used for pharmacology are undergoing several improvements [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, pharmacology is a mainstream basic science in the study of Medicine and is one of the crucial subjects found in basic and clinical medical curricula [4][5][6][7][8][9]. However, teaching and learning pharmacology is a complex task.…”
Section: Introductionmentioning
confidence: 99%
“…However, some innovative methods such as problem-based learning (PBL), casebased learning, clinical case presentations and seminars are being exercised by few institutes. 4 The undergraduate teaching in pharmacology has changed in recent years with adoptions of new methods that focus on supportive learning through novel teaching approaches like small group discussions, role plays, computer assisted learning (CAL), using audio-visual (A-V) aids, clinical pharmacology studies etc. These are being adopted by more and more medical colleges at both the undergraduate and postgraduate levels.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical pharmacology exercises include rational prescribing, adverse drug reaction (ADR) monitoring, pharmacokinetic calculations, pharmacodynamic toxicity, drug interactions and pharmacotherapeutics. 4 A seamless progression from basic principles through clinical pharmacology and then on to applied therapeutics has been suggested to be beneficial for medical students regarding proper teaching of pharmacology. 7 The instructional methods used to teach pharmacology in our institution include lectures, tutorials, and practical sessions such as prescription writing, criticism on rationality of prescriptions, pharmacy practicals and demonstration of experimental pharmacology with CAL using A-V aids or using live animals.…”
Section: Introductionmentioning
confidence: 99%